Peran Grit dalam Pendidikan: Sebuah Tinjauan Literatur yang Sistematis - Layyinah; Sumiati , Neneng Tati; Zahrotun Nihayah; Syaiim Framita, Gusty (Universitas Darul Ulum, 2025)
Completing studies in college is not an easy thing. Every student studying in college will be faced with lecture challenges such as; doing assignments, exams, quizzes, and research, and there are even students who participate in organizations and work. This study aims to investigate academic grit in university students. A systematic literature review was conducted using the Preferred Reporting Item for Systematic Reviews and Meta-Analyses (PRISMA) or (SLR), the search was conducted using Google Scholar and Elsevier databases. Based on the results of 6 literature that have been carried out, 5 articles found that every student needs high grit in the academic field, while 1 other article states that there is no difference in the level of grit in gender differences. Grit is an important non-cognitive factor that helps students face and overcome academic challenges. Students who have grit tend to keep trying to achieve goals despite facing difficulties, and use challenges as motivation to rise and achieve.